Sacral Insufficiency Fracture on Ga-68-DOTATATE PET/CT - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2021)
Ga-68-DOTATATE PET/CT is an important tool for imaging neuroendocrine tumors, including skeletal metastases. However, false-positive results can occur in inflammatory pathologies such as sacral insufficiency fracture. We report the case of a 47-year-old man who was diagnosed with a neuroendocrine tumor of the pancreas. Ga-68-DOTATATE PET/CT showed Ga-68-DOTATATE uptake at the right side of the sacrum. Afterward, MRI made the diagnosis of sacral insufficiency fracture.
Keywords: Ga-68-DOTATATE; insufficiency fracture; PET/CT; sacrum; FDG-PET/CT